An Immunologic Mode of Multigenerational Transmission Governs a Gut Treg Setpoint - Ramanan, Deepshika; Sefik, Esen; Galván-Peña, Silvia; Wu, Meng; Yang, Liang; Yang, Zhen; Kostic, Aleksandar; Golovkina, Tatyana V; Kasper, Dennis L; Mathis, Diane; Benoist, Christophe (Cell, 2020)
At the species level, immunity depends on the selection and transmission of protective components of the immune system. A microbe-induced population of RORγ-expressing regulatory T cells (Tregs) is essential in controlling gut inflammation. We uncovered a non-genetic, non-epigenetic, non-microbial mode of transmission of their homeostatic setpoint. RORγ Treg proportions varied between inbred mouse strains, a trait transmitted by the mother during a tight age window after birth but stable for life, resistant to many microbial or cellular perturbations, then further transferred by females for multiple generations. RORγ Treg proportions negatively correlated with IgA production and coating of gut commensals, traits also subject to maternal transmission, in an immunoglobulin- and RORγ Treg-dependent manner. We propose a model based on a double-negative feedback loop, vertically transmitted via the entero-mammary axis. This immunologic mode of multi-generational transmission may provide adaptability and modulate the genetic tuning of gut immune responses and inflammatory disease susceptibility.